Network management: Governance mechanisms, opportunities and contradictions - Vuorinen, Tero; Kurki, Tero (Piccola Impresa / Small Business, 2012)
This paper aims to describe different governance mechanisms and the opportunities and contradictions related to their application in network management. Three general governance mechanisms: market, hierarchy and trust have been identified in previous studies. The study advances the discussion of the application of governance mechanisms by comprehensively describing four network relationships and their governance mechanisms. Additionally, the influence of governance mechanisms to SMEs is discussed.